2011
DOI: 10.1111/j.1365-2702.2011.03911.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of Singaporean parental experiences in managing school‐aged children’s postoperative pain: a descriptive qualitative approach

Abstract: Nurses need to provide parents with support and education to facilitate their roles and improve their child's postoperative pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(104 citation statements)
references
References 47 publications
4
95
0
1
Order By: Relevance
“…Previous researchers have found that parents often ask for additional information, guidance, and support from health professionals, especially regarding their children's pain management. 8,22 The nature and amount of information delivered were determined according to an assessment of the mothers' information needs and the results of a pilot study. However, the mothers' needs were more varied than we anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have found that parents often ask for additional information, guidance, and support from health professionals, especially regarding their children's pain management. 8,22 The nature and amount of information delivered were determined according to an assessment of the mothers' information needs and the results of a pilot study. However, the mothers' needs were more varied than we anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…, Lim et al . ). Thus, it is important to provide educational intervention about postoperative pain management for parents whose children undergo inpatient elective surgery.…”
Section: Introductionmentioning
confidence: 97%
“…Parents also act as an advocate (Lim et al . ) who help to inform health professionals about their child's needs, such as asking for pain medication (Sng et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In a descriptive qualitative study aimed at understanding parents' experiences managing children's postoperative pain at a Singapore pediatric hospital, Lim et al (2012) report that factors affecting parental 108 participation in care included support from nurses, children's age, knowledge deficit, and nurses' busy schedules. These authors conclude that nurses need to provide parents with support and education in order to facilitate their roles and improve their child's postoperative pain management.…”
Section: Participation/involvementmentioning
confidence: 99%